Current status of molecular diagnostics for lung cancer - Evgeny N. Imyanitov; Elena V. Preobrazhenskaya; Sergey V. Orlov (Open Exploration Publishing Inc., 2024)
The management of lung cancer (LC) requires the analysis of a diverse spectrum of molecular targets, including kinase activating mutations in EGFR, ERBB2 (HER2), BRAF and MET oncogenes, KRAS G12C substitutions, and ALK, ROS1, RET and NTRK1-3 gene fusions. Administration of immune checkpoint inhibitors (ICIs) is based on the immunohistochemical (IHC) analysis of PD-L1 expression and determination of tumor mutation burden (TMB). Clinical characteristics of the patients, particularly age, gender and smoking history, significantly influence the probability of finding the above targets: for example, LC in young patients is characterized by high frequency of kinase gene rearrangements, while heavy smokers often have KRAS G12C mutations and/or high TMB. Proper selection of first-line therapy influences overall treatment outcomes, therefore, the majority of these tests need to be completed within no more than 10 working days. Activating events in MAPK signaling pathway are mutually exclusive, hence, fast single-gene testing remains an option for some laboratories. RNA next-generation sequencing (NGS) is capable of detecting the entire repertoire of druggable gene alterations, therefore it is gradually becoming a dominating technology in LC molecular diagnosis.